Aplikasi Radiasi Ionisasi dalam Pemuliaan Tanaman: Analisis Dosis dan Respons Biologis - Aryani, Ni Putu Hipumi Tribuana; Adelia, Kadek Ayu Cintya; Ety Kurniati (Magnetic: Research Journal of Physics and It’s Application, 2026)
The use of radiation on plants has varying effects depending on the type of radiation and dose given. This research aims to provide insight into the potential and effects of using radiation in plant breeding and its impact on the physiological and morphological characteristics of plants. This study examines various previous research on the application of radiation rays to horticultural plants, food plants and ornamental plants. The radiation used includes gamma rays, X-rays, sunlight and corona glow discharge plasma. The research results show that radiation can increase genetic diversity and influence plant growth characteristics such as plant height, number of leaves, and chlorophyll content. The right dose of radiation can produce superior varieties with desired characteristics. However, doses that are too high can reduce the survival rate and regeneration capacity of plants.